Existence, Uniqueness and Stability Results for Nonlocal Fractional Nonlinear Volterra-Fredholm Integro Differential Equations - Hamoud, Ahmed A.; Mohammed, Nedal M.; Ghadle, Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we prove the existence and uniqueness of solutions for a class of nonlinear fractional Volterra-Fredholm integro differential equations with nonlocal conditions. In addition, the Ulam-Hyers and Ulam-Hyers-Rassias stability for solutions of the given problem are also discussed. The desired results are proved by using Pachpatte’s integral inequality, aid of fixed point theorems due to Banach and Schaefer’s fixed point theorems.